Tertiary lymphoid structures in esophageal cancer: a novel target for immunotherapy - Zhai, Ke; Ma, Yuting; Gao, Xue; Ru, Kun; Zhao, Miaoqing (Frontiers in Immunology, 2025)
Esophageal cancer (EC), especially esophageal squamous cell carcinoma (ESCC), which is the most common subtype in China, is one of the most aggressive gastrointestinal malignancies. Traditional treatments like surgery, radiotherapy, and chemotherapy have limited success, but the study of tertiary lymphoid structure (TLS) has opened new avenues for immunotherapy. TLS is an ectopic immune cell cluster, including B cells, T cells, and dendritic cells (DCs), that forms in chronic inflammation such as tumors. TLS is often found at tumor invasion margins and is linked to better prognosis in EC patients, with higher TLS density and maturation associated with prolonged survival. TLS can also serve as a biomarker to assess immunotherapy outcomes. Further exploration of TLS molecular mechanisms could innovate EC treatments, especially by inducing TLS formation to improve therapy. This review summarizes the characteristics of TLS in EC, clinical findings, and the limitations and directions of current research, offering insights for future immunotherapy strategies.